Role of miR-200c in Myogenic Differentiation Impairment via p66Shc: Implication in Skeletal Muscle Regeneration of Dystrophic mdx Mice. (13th February 2018) - D'Agostino, Marco; Torcinaro, Alessio; Madaro, Luca; Marchetti, Lorenza; Sileno, Sara; Beji, Sara; Salis, Chiara; Proietti, Daisy; Imeneo, Giulia; C. Capogrossi, Maurizio; De Santa, Francesca; Magenta, Alessandra
Abstract : Duchenne muscular dystrophy (DMD) is a genetic disease associated with mutations of Dystrophin gene that regulate myofiber integrity and muscle degeneration, characterized by oxidative stress increase. We previously published that reactive oxygen species (ROS) induce miR-200c that is responsible for apoptosis and senescence. Moreover, we demonstrated that miR-200c increases ROS production and phosphorylates p66Shc in Ser-36. p66Shc plays an important role in muscle differentiation; we previously showed that p66Shc −/− muscle satellite cells display lower oxidative stress levels and higher proliferation rate and differentiated faster than wild-type ( wt ) cells. Moreover, myogenic conversion, induced by MyoD overexpression, is more efficient in p66Shc −/− fibroblasts compared to wt cells. Herein, we report that miR-200c overexpression in cultured myoblasts impairs skeletal muscle differentiation. Further, its overexpression in differentiated myotubes decreases differentiation indexes. Moreover, anti-miR-200c treatment ameliorates myogenic differentiation. In keeping, we found that miR-200c and p66Shc Ser-36 phosphorylation increase in mdx muscles. In conclusion, miR-200c inhibits muscle differentiation, whereas its inhibition ameliorates differentiation and its expression levels are increased in mdx mice and in differentiated human myoblasts of DMD. Therefore, miR-200c might be responsible for muscle wasting and myotube loss, most probably via a p66Shc-dependent mechanism in a pathological disease such as DMD.